DEPICTION OF SELF-ACCEPTANCE IN PERSONS WITH DISABILITIES NON-GENETICS IN TUBAN DISABILITY ORGANIZATION - Ruszahidah, Emylia; Moh. Ubaidillah Faqih,, Suhartono; Nur Faizah, Hanim (Indonesian Journal of Community Health Nursing, 2024)
Introduction: This study aims to (1) analyze the process or dynamics of self-acceptance in people with non-genetic disabilities and (2) analyze aspects that affect the process of self-acceptance. Methods: Case study research is a type of descriptive qualitative research. The data collection technique used in this study was a semi-structured interview. The data analysis used is assisted by the process of data reduction, data presentation and data verification. To measure the validity of this study, researchers used the theory trianggulation technique which compares information from different theoretical points of view. Results: The results showed that the process or dynamics of informant self-acceptance was influenced by self-acceptance, self-adjustment, self-satisfaction, and feelings of friendship with others. In addition, in this study it was found that help from family and people around the informant also affected self-acceptance of the informant. Conclusion: From the description above, it can be concluded that the process or dynamics of self-acceptance in people with non-genetic disabilities is influenced by many factors. Keywords: self-acceptance, people with non-genetic disabilities, adolescents